LIFE HACKS FOR NON-ENGLISH-SPEAKING LIBRARIANS: FEATURES OF COMMUNICATIVE PRACTICE IN TRANSLATION - OSADCHYI, Vitalii (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
Objective. This paper aims to provide practical recommendations to the non-English-speaking staff working at academic libraries to practice the English language in order to fully utilize the potential of global indexing services such as Scopus and Web of Science. Methods. Comparative analysis and bibliometric analysis were employed to estimate the share of the English-language journals in the aforementioned databases to emphasize the relevance of proper knowledge of English by academic librarians given its current status as the language of global scientific communication. Results. The analysis results revealed that as of August 2021, 56 % of the Scopus-indexed journals were published in the English language only while most of the rest practiced a hybrid language approach allowing their authors to submit papers in two/three languages. In contrast, only 7 journals (0.016 % in the cited database) published their materials in the Ukrainian language only. This indirectly testifies to the importance for scientists in Ukraine to report their findings in English to reach a wider target audience. This assumption may underlie the fact that all the 15 Ukrainian journals newly accepted in the Scopus database (as of Aug 2021) are all hybrid, that is, the papers are published both in English and Ukrainian. Conclusions. It is a relevant task both for researchers in Ukraine and academic librarians at Ukrainian universities to practice their knowledge of the English language given its current status as the language of global science. A practical way to do it is to engage local professional translators (preferably with certified teaching experience) who have confirmed their knowledge of academic English to conduct sessions for librarians to train their practical skills in speaking (at international conferences) and writing (when submitting papers to relevant journals). This work provides a reference framework for such attempts.